Position-specific fielding instances and utilisation in professional men`s T20 cricket - Lee, T. A.; Novak, A. R.; Pickering Rodriguez, E. C. (International Journal of Performance Analysis in Sport, 2026)
This descriptive study quantified the position of the first fielder involved in each delivery (primary fielding instances) in men`s professional Twenty20 (T20) cricket, focusing on data from 1964 individual deliveries during the 2022/23 Australian Big Bash League. Variables considered included game phase, non-fielder events, bowling type, primary fielding instance position and all fielding positions. Primary fielding instances were classified by position, bowling type and game phase. Positional utilisation was also examined, quantifying primary fielding instances relative to how often a fielding position formed part of the fielding setup. In-fielders accounted for 63% of all primary fielding instances, with the wicketkeeper (16.4%, n = 277) and bowler (10.2%, n = 172) most involved. However, outfielders ranked in five of the top ten positions by utilisation. Notably, primary fielding instances to deep-third and fine-leg were more frequent for pace bowlers (n = 63) than spin-in (n = 1) or spin-away (n = 0). For spin bowlers, a higher frequency of fielding instances were observed on the side of the field that aligned with the direction of spin. The insights gained from fielder placement based on competency and specific fielding activities may enhance T20 strategies to reduce opposition runs. Further research could help assess the effectiveness of these fielder placements.